2013
DOI: 10.4103/0970-4388.112397
|View full text |Cite
|
Sign up to set email alerts
|

Dental anxiety prediction using Venham Picture test: A preliminary cross-sectional study

Abstract: Anxiety or fearfulness affects a child's behavior, and to a large extent, determines the success of a dental treatment. It is essential to identify anxious children at the earliest age possible rather than simply deal with them later. It is crucial that every effort be made to ensure a positive experience for each child patient. Appropriate acknowledgment of patient's anxiety can solidify their confidence and allows the pediatric dentist an informed review of potential management options specific to every indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 0 publications
0
17
0
3
Order By: Relevance
“…Among these factors, indirect fear -the fear that the child perceives in those surrounding him or being passed through reports -accounts for most of this anxiety [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Among these factors, indirect fear -the fear that the child perceives in those surrounding him or being passed through reports -accounts for most of this anxiety [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other reports have found no difference in the severity of dental anxiety between age groups . Interestingly, certain other reports concluded that dental anxiety increases with age .…”
Section: Discussionmentioning
confidence: 67%
“…[123] Among these, in most of the reported cases (16 out of 24 case reports), the lower lip was the most common site for the embedded incisor fragment. [1,3,4,9,1117,19,20,22,23] However, Kalra et al ,[10] Cubukcu et al ,[18] and Agarwal et al [2] reported cases with tooth fragments embedded in the upper lip. McDonnell and McKiernan (in 1986)[7] and Hill et al [6] published case reports of tooth fragments embedded in the tongue.…”
Section: Discussionmentioning
confidence: 99%
“…If laceration and bleeding make clinical examination difficult, simple soft tissue and occlusal radiographs should be taken to help detect tooth fragments entrapped in the oral soft tissues. [2,18,23] Once the embedded tooth is diagnosed on radiographs, complete removal of the fractured tooth fragment is important to prevent infection, disfiguring, scarring and discoloration of the skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation